Different chromosome numbers but slight morphological differentiation and genetic admixture among populations of the Pulmonaria hirta complex (Boraginaceae). Issue 5 (5th May 2022) - Liu, Lijuan; Astuti, Giovanni; Coppi, Andrea; Peruzzi, Lorenzo
Abstract: Hybridization and introgression have a significant impact on the taxonomically controversial genus Pulmonaria . Within this genus, the P. hirta complex shows puzzling systematic relationships among P. hirta s.str. (2 n = [22, 26] 28), P. apennina (2 n = 22 [26]), and P. vallarsae (2 n = 22), showing range overlaps and mixed phenotypes in southern Europe. We carried out morphometric analyses of basal leaves and flower features along with AFLP characterization of 236 plants belonging to 11 populations within the complex and 1 population of P. officinalis . We also implemented an already available phylogeny with sequences from our target populations and characterized their karyotype. For all the populations within the complex, we found molecular evidence of a hybrid origin involving species belonging to different clades (angustifolia and officinalis clades). However, there is a certain morphological differentiation between some populations ("hirtoid" morph) and others ("vallarsoid" morph), albeit single individuals or entire populations show intermediate features. According to our results, hybridization and/or backcrossing/introgression have occurred, and gene flow is currently taking place among these "taxa". Following the hybridization event(s), we can elaborate three possible evolutionary scenarios: (1) one hybrid "vallarsoid" (2 n = 22) species spread across the Italian peninsula, and from this originated the "hirtoid" morph (2 n = 28) through dysploidy; (2) two geographically distinct hybridization events produced both "vallarsoid" and "hirtoid" morphs; (3) one "hirtoid" alloploid hybrid species originated and backcrossed with P. officinalis generating "vallarsoid" plants. Under scenarios 1 and 2, the different morphs met again in central Italy, with massive current gene flow. Under scenario 3, "vallarsoid" plants spread across the Italian peninsula, but further backcrossed with "hirtoid" plants in central Italy, leaving pure lineages of "vallarsoid" plants only in the extreme north and south of their range. This latter scenario is supported by populations with 2 n = 22, 26 chromosomes, having karyotype asymmetry indices intermediate between those of 2 n = 16 and 2 n = 28 cytotypes. Irrespective of the evolutionary dynamics, today, a single lineage showing three cytotypes occurs throughout the Italian peninsula, supporting the circumscription of a single polymorphic species, namely P. hirta .